The dual-hormone hypothesis and first-time fathers’ relationship satisfaction at 3 months postpartum - Donovan, Rylei L.; Corpuz, Randy (Frontiers in Psychology, 2025)
Human males face tradeoffs in how they invest resources toward mating and parenting. Research on male’s transition to fatherhood has revealed shifts in hormones tied to these tradeoffs. While work has focused on the influence of hormones on parenting during this stage, less is known about how these hormones influence mating (i.e., relationship functioning with partner) in the postnatal period. A father’s relationship satisfaction is expected to be related to endocrine activity across the transition to parenthood. We predicted that first-time fathers with high testosterone (T) would report lower relationship satisfaction. We expected this effect to be amplified (moderation) for those males with lower cortisol (CORT) levels (i.e., dual hormone hypothesis). At 3 months postpartum we measured salivary T and CORT (n = 220) and recorded relationship satisfaction using the Investment Model Scale (IMS). We found that fathers with high T and low CORT had the highest relationship satisfaction. While the effect was small, these findings ran counter to our predictions. We speculate that higher T and lower CORT males may report increased satisfaction as they support, retain, and secure additional opportunities from a mate who recently demonstrated her ability (and willingness) to produce offspring. Discussion focuses on numerous limitations of the study, small effect size, and the need for replication with less homogenous samples.